Muscle fiber conduction velocity and selected biomotor abilities in soccer players - Kurz, E.; Pröger, S.; Gizzi, L.; Schwesig, R.; Delank, K. S.; Bartels, T. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Higher muscle fiber conduction velocities (CV) were related to the training status. Within trained participants, sprinters showed higher CV than endurance runners. Based on the muscle fiber CV, the cross-section of the muscle fibers can be estimated. Muscle fibers with a larger cross-sectional area would suggest a higher distribution of type II (fast-twitch) fibers. The aim of this study was to examine the selective influences of muscle fiber CV on strength, speed, and endurance test results in soccer players.